Attitudes of parents in Jerusalem towards teaching non-Palestinian curricula (Israeli, British, American, and German) - Al-Essa, Enas Abbad; Kamal, Nor (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the attitudes of the parents in East Jerusalem towards registering their children in non-Palestinian curricula. This was done by examining the motives and reasons that affect the parents’ decisions and examining the impact of each of parents’ gender, scientific qualification, the type of secondary education certificate and the economic level variables on their attitudes towards registering their children in non-Palestinian curricula. The study targeted a sample of parents in different schools in Jerusalem through distributing a questionnaire to be filled in paper or electronically, the sample reached 89 participants. The data were analyzed using the SPSS software in order to obtain the results. According to the results of the study, Palestinian and Israeli curricula were chosen by parents to facilitate enrollment in universities inside the country, while the results indicated that parents see that the Israeli, British and American curriculum were chosen to prepare students for university study and enabling them to choose disciplines that keep pace with scientific progress. Parents also think that the American curriculum facilitates the enrollment of their children to study abroad. The sample, which participated in the selection of the German curriculum, believed that it enhances individual autonomy and it is based on analysis. Moreover, the study indicated that there were differences between the average responses of the respondents due to the gender variable and was in favor of males in the sample. Thus, the first hypothesis was rejected meanwhile the rest of the hypotheses were accepted. There are no statistically significant differences in the responses of the respondents due to parents’ academic qualification, the type of secondary education certificate, and the economic level variables. Where the German curriculum is based on analysis and application of concepts with a response rate of 95% and that it supports positive values ​​and trends towards society and helps prepare the student for university study with a response rate of 90%. For the student to choose majors that keep pace with scientific progress,The study recommends re-conducting the research on a larger sample and using the mixed research methodology.